ANALISIS USAHATANI PEPAYA DI KABUPATEN MUARO JAMBI - Refa’ul Khairiyakh (Universitas Wahid Hasyim, 2014)
This research aimed to determine farm income and feasibility of papaya in Muaro Jambi Regency. The data is used on this research is primary data that gotten from interview to 33 sample of farmer. Farm income of papaya calculated use farm analysis Pd=TR – TC, whereas to know farm feasibility of papaya is used two criteria, those are R/C ratio and BEP price of papaya. From the research, it is known that average of farm income of papaya is Rp. 27.907.570,- per year per land area with the profit is Rp. 15.008.933,- per year per land area. Papaya farm in Muaro Jambi Regency is feasible with the value of R/C ratio by 3, 2 and the price of papaya in farmer level is higher than the price of Break Even Point with the average of price by Rp. 4.750. Keywords: BEP, income, papaya, R/C